The effects of adolescents' sleep duration on life satisfaction: utilizing the autoregressive cross-lagged (ARCL) model - Jung, Eun Jin (Frontiers in Sleep, 2025)
IntroductionSleep duration in youth is a key factor that significantly influences mental health. However, there have been limited studies examining the direct impact of adolescents' sleep on life satisfaction. This study aims to analyze the effects of adolescents' sleep duration on their life satisfaction.MethodsFor this purpose, data from the Korean Children and Youth Panel Survey (KCYPS) conducted by the National Youth Policy Institute (NYPI) were utilized, specifically focusing on the 4th-grade panel data (N = 2,378; 52.4% male; 47.6% female). Analysis revealed a rapid decline in youth sleep duration upon entering junior high school. Consequently, the data were categorized into two periods for analysis: Year I (4th grade) to Year IV (7th grade), and Year IV (7th grade) to Year VII (10th grade).ResultsUsing the autoregressive cross-lagged (ARCL) model, it was found that sleep duration during Years IV-VII significantly influenced life satisfaction over time. An increase in sleep duration led to a subsequent increase in life satisfaction over time with statistical significance. Specifically, sleep duration during 7th grade exhibited a significant static influence on life satisfaction at 8th grade (β = 0.025, p < 0.03), while sleep duration during 8th grade statically affected life satisfaction during 9th grade (β = 0.026, p < 0.03). Moreover, sleep duration at 9th grade had a static influence on life satisfaction during 10th grade, with statistical significance (β = 0.027, p < 0.03).DiscussionBased on the findings of this study, implications and suggestions for future research were discussed. It is essential to create an environment that promotes adequate sleep for adolescents, even after they enter junior high school.